Lecanicillium subprimulinum (Cordycipitaceae, Hypocreales), a novel species from Baoshan, Yunnan - Huang, Shike; Maharachchikumbura, Sajeewa S.n.; Jeewon, Rajesh; Bhat, D Jayarama; Phookamsak, Rungtiwa; Hyde, Kevin D; Al-Sadi, Abdullah M.; Kang, Jichuan (Phytotaxa, 2018)
In this paper, we report a new asexual-morph taxon belonging to the family Cordycipitaceae (Hypocreales), which is associated with a sexual morph of an ophioceras-like taxon on submerged wood collected from Baoshan, Yunnan, China. Morphologically, this new taxon is similar to known asexual morphs of Lecanicillium and characterized by conidiophores arising from hyaline hyphae, with gregarious, ellipsoid to ovoid, aseptate conidia. Phylogenetic analyses of a combined LSU, SSU, tef1-α and ITS sequence dataset positions our taxon in Cordycipitaceae and close to Lecanicillium sp. (CBS 639.85) and L. primulinum. Lecanicillium subprimulinum is introduced as a new species with support from molecular data.